PAYUNG DALAM KARYA LUKIS SUREALIS - NOVRIKO DARMA, Yasrul Sami, S.Sn., M.Sn., Drs. Abd. Hafiz, M.Pd. (Serupa The Journal of Art Education, 2017)
The porpuses to explores the lives of the leaders with an umbrella metaphor, in daily life into the work of Surealis painting. Here umbrella related to leadership style, government, and politics, while the umbrella in the metaphor right into leadership. While many leaders who abuse their powers so that a leader is able to do whatever he wants even do crime and corruption. The mekhod of creation work art are, preparation, elaboration, synthesis, concept realitation and completion. Making this thesis aims to visualize the umbrella in the work of surealispainting, the resulting work : Rancak dari Ateh, Mencari Jalan, Bebas, Bersaing, Menampung, Penguasa, Taktik, Menggapai, Berawal dari Kata, Asli atau Palsu.Kata Kunci : Payung, Lukis, Surealis